Kedudukan Notaris yang diangkat berdasarkan Surat Edaran Kementerian Hukum dan HAM Nomor AHU-AH.02-37 Tahun 2024 - Dandi Tisna Satria (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
A notary is a public official who has the authority to make authentic deeds and serve the interests of the community who is appointed and dismissed by the Minister. So in this case the Notary as a public official has a big responsibility to provide legal certainty to the public through authentic deeds. The appointment of a notary as a public official here must be based on the Notary Position Law and Minister of Law and Human Rights Regulation Number 19 of 2019. The issuance of the Ministry of Law and Human Rights Circular Letter Number AHU-AH.02-37 of 2024 has resulted in irregularities in its issuance and has become a problem for notaries who has not been appointed or has been appointed and the validity of the Notary's appointment can be questioned if the Notary's appointment is valid due to the Law on the Position of Notaries and the Minister of Law and Human Rights Regulation which is A higher score cannot be a valid condition for the appointment of a Notary Public. In this case, the position of the Circular Letter issued has a hierarchy which is not a statutory regulation because it is only a guideline, direction and confirmation of its binding force only internally and its position must not conflict with higher regulations. This research uses normative law, namely research carried out by examining library materials or secondary legal materials and approaching the problem based on laws and a conceptual approach. The results of the research show that the basis for appointing a Notary Public is invalid because it must be based on the Notary Position Law and Permenkumham 19/2019, not based on the Circular Letter of the Ministry of Law and Human Rights Number AHU-AH.02-37 of 2024. So the Code of Ethics test is organized by the Ministry is invalid and invalid even though it was formed based on the authority of the Minister but is in conflict with regulations and laws which have a higher position.